Relationship between prehypertension and chronic kidney disease in middle-aged people in Korea: the Korean genome and epidemiology study - Kim, Min-Ju (BioMed Central, 2012)
BACKGROUND: Elevated blood pressure (BP) is a major risk factor for the progression of chronic kidney disease (CKD). However, little is known about the influence of prehypertension on CKD. In this study, we investigated the relationship between prehypertension and CKD in a middle-aged Korean population. Furthermore, we prospectively evaluated the effect of active BP control on deterioration of kidney function during the two-year follow-up. METHODS: The Korean Genome and Epidemiology Study is a community-based prospective cohort study started in 2001, with a follow-up survey conducted every two years. A total of 9509 participants aged 40–69 years were included in a baseline study. BP was classified according to the Seventh Report of the Joint National Committee on High BP (JNC-7) categories and CKD was defined as the presence of proteinuria or eGFR< 60mL/min/1.73m(2). A multivariable logistic regression model was used to identify associations between BP and CKD. RESULTS: The overall prevalence of CKD was 13.2%, and significantly increased with BP level. The multivariable-adjusted odds ratio of CKD was 1.59 for prehypertension and 2.27 for hypertension, compared with a normal BP. At the two-year follow-up, among the participants with prehypertension, subjects whose BP was poorly controlled had a significantly higher risk of eGFR drop (OR, 1.37; 95% CI, 1.13-1.67), as compared to controls. The prevalence of eGFR drop was 57.8% in the controlled BP group and 66.0% in the poorly-controlled BP group. CONCLUSIONS: Prehypertension, as well as hypertension, is significantly associated with CKD among middle-aged Koreans. Our results indicate that active control of the blood-pressure of prehypertensive individuals is needed to prevent deterioration of kidney function.